Neutrophil-to-Lymphocyte Ratio on Admission is an Independent Risk Factor for the Severity of Neurological Impairment at Disease Onset in Patients with a First Episode of Neuromyelitis Optica Spectrum Disorder - Zhou Y (Dove Medical Press, 2021)
Yongyan Zhou, Haojie Xie, Yi Zhao, Jinwei Zhang, Yanfei Li, Ranran Duan, Yaobing Yao, Yanjie Jia Department of Neurology, The First Affiliated Hospital of Zhengzhou University, Zhengzhou, People’s Republic of ChinaCorrespondence: Yanjie JiaDepartment of Neurology, The First Affiliated Hospital of Zhengzhou University, Erqi District, Zhengzhou City, Henan Province, People’s Republic of ChinaTel +861 351 380 2916Email jiayanjie1971@zzu.edu.cnPurpose: To investigate the relationship between the neutrophil-to-lymphocyte ratio (NLR) and the severity of neurological impairment at disease onset in patients with a first episode of neuromyelitis optica spectrum disorder (NMOSD).Patients and Methods: This retrospective study included 259 patients with newly diagnosed NMOSD who were hospitalized at our institution between January 2013 and January 2020 (NMOSD group) and 169 healthy control subjects who underwent a physical examination at our hospital during the same period (control group). The clinical data collected included general information, past medical history, biochemical test results, imaging findings, NLR, AQP-4 antibody status, and initial Expanded Disability Status Scale score. A logistic regression model was used to analyze NLR as an independent risk factor for the severity of neurological impairment at disease onset in the NMOSD group. Receiver-operating characteristic curve analysis was used to evaluate the ability of the NLR to predict the severity of neurological impairment at disease onset in the NMOSD group and to determine its critical value.Results: The NLR was significantly higher in the NMOSD group than in the control group (P< 0.001). In the NMOSD group, neurological impairment at disease onset was more severe in those with a high NLR than in those with a low NLR (P< 0.001). At onset of disease, patients with severe neurological impairment had a more significant increase in NLR than those with mild-to-moderate neurological impairment (P< 0.001). Both univariate (OR 1.180, 95% CI 1.046– 1.331, P=0.007) and multivariate (OR 1.146, 95% CI 1.003– 1.308, P=0.044) logistic regression analyses showed that the NLR was positively correlated with the severity of neurological impairment at onset of disease in the NMOSD group. The area under the receiver-operating characteristic curve was 0.687.Conclusion: The NLR is an independent risk factor for the severity of neurological impairment at disease onset in patients with a first episode of NMOSD.Keywords: neuromyelitis optica spectrum disorder, neutrophil-to-lymphocyte ratio, first episode, severity, Expanded Disability Status Scale score